Factor Proportions, Human Capital and Foreign Trade: The Case of West Germany Reconsidered - Roskamp, Karl W.; McMeekin, Gordon C. (Quarterly Journal of Economics, 1968)
Introduction, 152. — Method of analysis, 153. — Determination of returns to human capital, 156. — Results of the study, 158. — Conclusion, 160.